SARS-CoV-2 pre-exposure prophylaxis with tixagevimab/cilgavimab (AZD7442) provides protection in inborn errors of immunity with antibody defects: a real-world experience - Pulvirenti, Federica; Garzi, Giulia; Milito, Cinzia; Sculco, Eleonora; Sciannamea, Maddalena; Napoli, Anna; Cinti, Lilia; Roberto, Piergiorgio; Punziano, Alessandra; Carrabba, Maria; Piano Mortari, Eva; Carsetti, Rita; et al. (Frontiers in Immunology, 2023)
Background. Preventive strategies against severe COVID-19 in Inborn Errors of Immunity (IEI) include bivalent vaccines, treatment with SARS-CoV-2 monoclonal antibodies (mAbs), early antiviral therapies, and pre-exposure prophylaxis (PrEP). Objective. To assess the effectiveness of the PrEP with tixagevimab/cilgavimab (AZD7442) in IEI with primary antibody defects during the COVID-19 Omicron wave. Methods. A six-month prospective study evaluated the SARS-CoV-2 infection rate and the COVID-19 severity in the AZD7442 group, in the no-AZD7442 group, and in a group of patients with a recent SARS-CoV-2 infection. Spike-specific IgG levels were measured at regular intervals. Results. Six out of thirty-three patients (18%) and 54/170 patients (32%) became infected in the AZD7442 group and in the no-AZD7442 group, respectively. Within 90 days post-administration, the AZD7442 group was 85% less likely to be infected and 82% less likely to have a symptomatic disease than the no-AZD7442 group. This effect was lost thereafter. In the entire cohort, no mortality/hospitalisation was observed. The control group of 35 recently infected patients was 88% and 92% less likely to be infected than the AZD7442 and no-AZD7442 groups. Serum anti-Spike IgG reached the highest peak seven days post-AZD7442 PrEP then decreased, remaining over 1000 BAU/mL 180 days thereafter. Conclusions. In patients with IEI and antibody defects, AZD7442 prophylaxis had a transient protective effect, possibly lost possibly because of the appearance of new variants. However, PrEP with newer mAbs might still represent a feasible preventive strategy in the future in this population.